The dignity of women and the female genius - Sánchez Barragán, Rosa De Jesús (2020)
The human person manifests itself through two ways of being: being a man or being a woman. Both are the same and at the same time different. The same because they enjoy the same human dignity that is given by being a person; and at the same time, they are different because they have qualities or gifts typical of their masculine or feminine genius, which is contributed from a biological, psychological, neuronal, etc. aspect. This difference constitutes a wealth for all humanity.